Looking back after 25 years Interview: Salim Lone, the first editor of Africa Recovery, at his home in Kenya - United Nations (Africa Renewal, 2012)
Salim Lone, who edited Africa Recovery during its first decade, looks back at the magazine’s early days. At his home in Nairobi, Kenya, he spoke with Africa Renewal’s managing editor, Ernest Harsch.